Evaluation of Chemical Acidizing Performance Using 15% Hydrochloric Acid (HCl) on Eight Production Wells in Field X - Arjuna; Hardi, Maulana; Kuswardani, Tyas; Wardani, Oktaviani Kusuma (Scientific Contributions Oil and Gas, 2026)
This study evaluates the performance of matrix acidizing, a stimulation process conducted below fracturing pressure using 15% hydrochloric acid (HCl) on eight production wells in Field X, a carbonate reservoir. The assessment compares pre‑ and post‑treatment production performance over a defined 30‑day monitoring period. Acid selection was supported by laboratory dissolution analysis using β₁₀₀ and dissolution rate indicators, demonstrating that 15% HCl provided the strongest dissolving power against carbonate minerals compared with formic and acetic acids. The distinction between chemical acidizing (acid-based mineral dissolution) and matrix acidizing (operational mode focused on restoring near‑wellbore permeability without inducing fractures) is clarified to align with standard acidizing terminology. Field results show a 90% overall success rate, with average production gains of +778.76 BFPD (fluid) and +49.54 BOPD (oil). One well exhibited an anomalous response, characterized by an increased fluid rate but a reduced oil rate, indicating the potential activation of water-conductive pathways. These findings highlight that, although acid strength is an important factor, treatment success also depends on reservoir heterogeneity, scale distribution, and the effectiveness of acid placement. The integrated workflow combining Scale Index (SI) evaluation with dissolving‑power‑based acid screening provides a structured approach for designing matrix acidizing in mature carbonate fields.